European Media: Structures, Policies and Identity - Stylianos Papathanassopoulos; Ralph Negrine (Polity, 2011)
European Media provides a clear, concise account of the structures, dynamics and realities of the changing face of media in Europe. It offers a timely and illuminating appraisal of the issues surrounding the development of new media in Europe and explores debates about the role of the media in the formation of a European public sphere and a European identity.The book argues that Europe offers an ideal context for examining interactions between global, regional and national media processes and its individual chapters consider: the changing structure of the European media; the development of new media; the Europeanization of the media in the region; the challenges for the content; and audiences. Special emphasis is given to the transformation of political communication in Europe and the alleged emergence of a European public sphere and identity. European Media: Structures, Politics and Identity is an invaluable text for courses on media and international studies as well as courses dealing with European and national policy studies. It is also helpful to students, researchers and professionals in the media sector since it combines hard facts with theoretical insight.